Colorectal cancer incidence, mortality, and stage distribution in European countries in the colorectal cancer screening era: an international population-based study. Issue 7 (July 2021) - Cardoso, Rafael; Guo, Feng; Heisser, Thomas; Hackl, Monika; Ihle, Petra; De Schutter, Harlinde; Van Damme, Nancy; Valerianova, Zdravka; Atanasov, Trajan; Májek, Ondřej; Mužík, Jan; Nilbert, Mef Christina; et al.
Summary: Background: Colorectal cancer screening programmes and uptake vary substantially across Europe. We aimed to compare changes over time in colorectal cancer incidence, mortality, and stage distribution in relation to colorectal cancer screening implementation in European countries. Methods: Data from nearly 3·1 million patients with colorectal cancer diagnosed from 2000 onwards (up to 2016 for most countries) were obtained from 21 European countries, and were used to analyse changes over time in age-standardised colorectal cancer incidence and stage distribution. The WHO mortality database was used to analyse changes over time in age-standardised colorectal cancer mortality over the same period for the 16 countries with nationwide data. Incidence rates were calculated for all sites of the colon and rectum combined, as well as the subsites proximal colon, distal colon, and rectum. Average annual percentage changes (AAPCs) in incidence and mortality were estimated and relevant patterns were descriptively analysed. Findings: In countries with long-standing programmes of screening colonoscopy and faecal tests (ie, Austria, the Czech Republic, and Germany), colorectal cancer incidence decreased substantially over time, with AAPCs ranging from −2·5% (95% CI −2·8 to −2·2) to −1·6% (−2·0 to −1·2) in men and from −2·4% (−2·7 to −2·1) to −1·3% (−1·7 to −0·9) in women. In countries where screening programmes were implemented during the study period, age-standardised colorectal cancer incidence either remained stable or increased up to the year screening was implemented. AAPCs for these countries ranged from −0·2% (95% CI −1·4 to 1·0) to 1·5% (1·1 to 1·8) in men and from −0·5% (−1·7 to 0·6) to 1·2% (0·8 to 1·5) in women. Where high screening coverage and uptake were rapidly achieved (ie, Denmark, the Netherlands, and Slovenia), age-standardised incidence rates initially increased but then subsequently decreased. Conversely, colorectal cancer incidence increased in most countries where no large-scale screening programmes were available (eg, Bulgaria, Estonia, Norway, and Ukraine), with AAPCs ranging from 0·3% (95% CI 0·1 to 0·5) to 1·9% (1·2 to 2·6) in men and from 0·6% (0·4 to 0·8) to 1·1% (0·8 to 1·4) in women. The largest decreases in colorectal cancer mortality were seen in countries with long-standing screening programmes. Interpretation: We observed divergent trends in colorectal cancer incidence, mortality, and stage distribution across European countries, which appear to be largely explained by different levels of colorectal cancer screening implementation. Funding: German Cancer Aid (Deutsche Krebshilfe) and the German Federal Ministry of Education and Research.